Effect of leukotriene B4 on arachidonate metabolism and activation of blood cells and endothelial cells - Wang Zhao-Yue; Chen De-Chun; He Yang; Li Fu-Gang; Ruan Chang-Geng (Acta Pharmacologica Sinica, 2016)
Leukotriene B4 (LTB4) induced human neutrophils (Neu) aggregation with thromboxane B2/prostaglandin E2 formation and lysozyme release, enhanced platelet aggregation and/or serotonin release caused by threshold concentrations of calcimycin or ADP, and increased Neu adherence to human umbilical vein endothelial cells. Some of its actions were inhibited by quercetin and cobra venom. These results indicate that LTB4 possesses pharmacological effects on blood cells as well as on endothelial cells, and would be useful for searching new type of anti-inflammatory drugs.